Synthesis and characterization of ABA‐type triblock copolymers derived from polyimide and poly(2‐methyl‐2‐adamantyl methacrylate). Issue 9 (21st January 2014) - Ando, Shota; Koyama, Yusuke; Miyata, Sou; Sato, Shuichi; Kanehashi, Shinji; Nagai, Kazukiyo
Abstract ABA‐type triblock copolymers derived from 4, 4‐(hexafluoroisopropylidene)diphthalic anhydride‐2, 3, 5, 6‐tetramethyl‐1, 4‐phenylenediamine and 2‐methyl‐2‐adamantyl methacrylate (2‐MAdMA) were synthesized via atom transfer radical polymerization. The component ratios of polyimide (PI) and poly(2‐MAdMA) (PMAdMA) were about 8/2, 6/4 and 3/7, as determined using 1H NMR spectroscopy and thermogravimetric analysis (TGA). The film structure of the triblock copolymers was dependent on the PI structure. Hydrophobicity increased as the component ratio of PMAdMA increased. Based on TGA, three‐step decomposition behaviors of all triblock copolymers derived from PI and PMAdMA in nitrogen and air atmosphere were observed. The gas permeability of the triblock copolymers was lower than that of PI. This finding can be attributed to the decrease in fractional free volume by the adamantane component and the decrease in permeability of the triblock copolymers compared with PI. The dielectric constant of the triblock copolymers was lower than that of PI. The dielectric constant was dependent on molar volume and molar porlarizability, and the dielectric constant derived from the symmetric structure of adamantane was reduced. The ABA‐type triblock copolymers derived from PI and PMAdMA can be considered as new polymer materials with high hydrophobicity, high H2/CO2 selectivity and low dielectric constant. © 2013 Society of Chemical Industry